2019
DOI: 10.1016/j.placenta.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Aldehyde dehydrogenase isoforms and inflammatory cell populations are differentially expressed in term human placentas affected by intrauterine growth restriction

Abstract: Objective: Intrauterine growth restriction (IUGR) is a complication of pregnancy that has both short-and long-term sequelae for affected mothers and offspring. The pathophysiology of disease stems from poor nutrient and oxygen provision to the fetus, resulting in increased oxidative stress within the placenta. As the milieu within the local microenvironment alters macrophage differentiation, we hypothesized that macrophage plasticity may be altered in placentas associated with IUGR, and that they would show ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 40 publications
2
9
0
1
Order By: Relevance
“…Thus, the consumption of higher levels of soybean oil could improve the rate of lipid oxidation, accumulation of free radicals into the cells causing cell damage and, consequently, the inflammatory condition that would lead to metabolic diseases such as type 2 diabetes and atherosclerosis [53]. These results confirm previous studies that identified the fatty aldehyde dehydrogenase isozymes, such as AL3A2, have cell-specific functions associated with inflammation, differentiation, or oxidative-stress responses [54,55].…”
Section: Different Levels Of Dietary Soybean Oil Modulate Gene Expres...supporting
confidence: 84%
“…Thus, the consumption of higher levels of soybean oil could improve the rate of lipid oxidation, accumulation of free radicals into the cells causing cell damage and, consequently, the inflammatory condition that would lead to metabolic diseases such as type 2 diabetes and atherosclerosis [53]. These results confirm previous studies that identified the fatty aldehyde dehydrogenase isozymes, such as AL3A2, have cell-specific functions associated with inflammation, differentiation, or oxidative-stress responses [54,55].…”
Section: Different Levels Of Dietary Soybean Oil Modulate Gene Expres...supporting
confidence: 84%
“…Edaravone is an established free radical scavenger which has a hydroxyl radical quenching effect and an inhibitory effect against peroxynitrite and peroxyl radicals [ 53 ]. One of the important factors leading to fetal growth restriction in preeclampsia is the increased production of placental oxidants due to increased maternal and fetal metabolism [ 10 , 48 ]. The role of antioxidants in management of placental ischemia-induced growth retardation and decreased placental weight has been investigated [ 36 , 43 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The significantly down-regulated gene HLA–DQA1 encodes a membrane-anchored protein for presenting peptides derived from extracellular proteins. It is mainly expressed in lymphocytes, dendritic cells, and macrophages; these antigen-presenting cells show altered plasticity in FGR placentas ( Freitag et al, 2014 ; Liu et al, 2015 ; Chu et al, 2019 ). In addition, HLA–DQA1 was involved in 8 of the top 10 KEGG pathways (see Supplementary Table 3 ), indicating that it is closely associated with FGR and fetal programming via immunologic processes.…”
Section: Discussionmentioning
confidence: 99%